The syndrome of deafness‐dystonia: Clinical and genetic heterogeneity. Issue 6 (15th February 2013) - Kojovic, Maja; Pareés, Isabel; Lampreia, Tania; Pienczk‐Reclawowicz, Karolina; Xiromerisiou, Georgia; Rubio‐Agusti, Ignacio; Kramberger, Milica; Carecchio, Miryam; Alazami, Anas M.; Brancati, Francesco; Slawek, Jaroslaw; Pirtosek, Zvezdan; et al.
ABSTRACT The syndrome of deafness‐dystonia is rare and refers to the association of hearing impairment and dystonia when these are dominant features of a disease. Known genetic causes include Mohr‐Tranebjaerg syndrome, Woodhouse‐Sakati syndrome, and mitochondrial disorders, but the cause frequently remains unidentified. The aim of the current study was to better characterize etiological and clinical aspects of deafness‐dystonia syndrome. We evaluated 20 patients with deafness‐dystonia syndrome who were seen during the period between 1994 and 2011. The cause was identified in only 7 patients and included methylmalonic aciduria, meningoencephalitis, perinatal hypoxic‐ischemic injury, large genomic deletion on chromosome 7q21, translocase of inner mitochondrial membrane 8 homolog A (TIMM8A) mutation (Mohr‐Tranebjaerg syndrome), and chromosome 2 open reading frame 37 (C2orf37) mutation (Woodhouse‐Sakati syndrome). The age of onset and clinical characteristics in these patients varied, depending on the etiology. In 13 patients, the cause remained unexplained despite extensive work‐up. In the group of patients who had unknown etiology, a family history for deafness and/or dystonia was present the majority of patients, suggesting a strong genetic component. Sensory‐neural deafness always preceded dystonia. Two clinical patterns of deafness‐dystonia syndrome were observed: patients who had an onset in childhood had generalized dystonia (10 of 13 patients) with frequent bulbar involvement, whereas patients who had a dystonia onset in adulthood had segmental dystonia (3 of 13 patients) with the invariable presence of laryngeal dystonia. Deafness‐dystonia syndrome is etiologically and clinically heterogeneous, and most patients have an unknown cause. The different age at onset and variable family history suggest a heterogeneous genetic background, possibly including currently unidentified genetic conditions. © 2013 Movement Disorder Society